Anastomotic techniques for oesophagectomy for malignancy: systematic review and network meta-analysis. Issue 4 (23rd May 2020) - Kamarajah, S K; Bundred, J R; Singh, P; Pasquali, S; Griffiths, E A
Abstract: Background: Current evidence on the benefits of different anastomotic techniques (hand-sewn (HS), circular stapled (CS), triangulating stapled (TS) or linear stapled/semimechanical (LSSM) techniques) after oesophagectomy is conflicting. The aim of this study was to evaluate the evidence for the techniques for oesophagogastric anastomosis and their impact on perioperative outcomes. Methods: This was a systematic review and network meta-analysis. PubMed, EMBASE and Cochrane Library databases were searched systematically for randomized and non-randomized studies reporting techniques for the oesophagogastric anastomosis. Network meta-analysis of postoperative anastomotic leaks and strictures was performed. Results: Of 4192 articles screened, 15 randomized and 22 non-randomized studies comprising 8618 patients were included. LSSM (odds ratio (OR) 0·50, 95 per cent c.i. 0·33 to 0·74; P = 0·001) and CS (OR 0·68, 0·48 to 0·95; P = 0·027) anastomoses were associated with lower anastomotic leak rates than HS anastomoses. LSSM anastomoses were associated with lower stricture rates than HS anastomoses (OR 0·32, 0·19 to 0·54; P < 0·001). Conclusion: LSSM anastomoses after oesophagectomy are superior with regard to anastomotic leak and stricture rates. Graphical Abstract: Stapled anastomoses were associated with lower anastomotic leak rates than hand-sewn anastomoses following oesophagectomy. Furthermore, linear stapled/semimechanical (LSSM) techniques were associated with lower rates of anastomotic stricture than circular stapled or hand-sewn anastomoses. Current evidence therefore suggests superiority for the LSSM technique for oesophagogastric anastomosis. Linear stapler techniques superior